Halal issues in pharmaceutical products: urgent need to have modern and efficient production of pharmaceuticals and biopharmaceuticals - Mel, Maizirwan; Mohd. Salleh, Hamzah (TM-Info-Media Sdn. Bhd., 2009)
In general, ingredients involved in pharmaceutical production can be sub-divided as (a) process materials {materials utilized in the production process, in R&D laboratory and manufacturing); (b) pharmaceutical excipients {inactive ingredients component included in the final pharmaceutical formulation); (c) active pharmaceutical ingredients, API (any substance or mixture of substances that is the active ingredient of the drug, intended to cause pharmacological activity or other direct effect in the diagnosis, cure, mitigation, treatment or prevention of disease or to affect the structure and function of the body}; and (d) analytical reagent {chemical substances that contain sufficient purity that can detect any chemical substances for chemical analysis}.